A ANALISIS STRATEGI PENANGANAN BIRD STRIKE DI BANDAR UDARA INTERNASIONAL ZAINUDDIN ABDUL MADJID LOMBOK DALAM MENINGKATKAN KESELAMATAN PENERBANGAN - Saputri, Joan Thalia; Agoes Soebagio; Yenni Arnas (Jurnal Teknologi Kedirgantaraan, 2025)
The rapid growth of air transportation in Indonesia presents challenges to flight safety, particularly the recurring threat of bird strikes. Zainuddin Abdul Madjid International Airport Lombok (BIZAM), as the primary aviation hub in West Nusa Tenggara, frequently experiences such incidents due to its proximity to bird-attracting environments such as grasslands, rice fields, and water bodies. This study aims to analyze the causes of bird strikes and evaluate current mitigation strategies. A qualitative descriptive method was employed, involving direct field observation, interviews with airport safety personnel, and review of internal documents such as bird strike logs and safety reports. The research was conducted during the author’s On-the-Job Training (OJT) at BIZAM for five months in 2024. The findings revealed three documented bird strike incidents during the observation period, occurring near the runway and apron areas during take-off and landing phases. While current deterrent measures such as vehicle patrols and sirens are in use, they are largely ineffective in the long term. The absence of real-time monitoring systems, data integration, and inter-agency collaboration contributes to the vulnerability. This study recommends the implementation of habitat management, predictive data modeling, and radar-based detection tools to enhance flight safety and align with international aviation standards.